On Colored Edge Cuts in Graphs - Faria, Luerbio; Klein, Sulamita; Sau, Ignasi; Souza, Uéverton S.; Sucupira, Rubens (Anais do Encontro de Teoria da Computação (ETC); 2016: Anais do I Encontro de Teoria da ComputaçãoDO - 10.5753/etc.2016.9764, 2016)
In this work we present some results on the classical and parameterized complexity of finding cuts in edge-colored graphs. In general, we are interested in problems of finding cuts {A,B} which minimize or maximize the number of colors occurring in the edges with exactly one endpoint in A.